Building Coalitions: Structure - Penne Smith; Charles H. Bell; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY504, Part 12 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.